Influence of Fortified Tempe with Iron and Vitamin A to Increase Hemoglobin Level of Rats with Iron Deficiency Anemia - Astuti, Rahayu; Subagyo, Hertanto Wahyu; Muis, Siti Fatimah; Widianarko, Budi (Pakistan Journal of Nutrition, 2017)
Objective: The study was conducted to assess the influence of fortified tempe with iron and vitamin A to increase hemoglobin level. Methodology: An experimental study of randomized pre test, post test and control group design was conducted on 30 Sprague-Dawley rats with iron deficiency anemia. Samples were divided into 6 groups randomly and then the rats were treated for 6 weeks. The treatments were as follows: (1) Standard feed (SF), (2) SF+TWF, (3) SF+TFe230, (4) SF+TFe271, (5) SF+TFe271+VA15 and (6) SF+TFe271+VA50, which TWF was tempe without fortification, TFe230 and TFe271 was tempe fortified with iron 230 and 271 ppm, VA15 was 15 ppm vitamin A and VA50 was 50 ppm vitamin A. Iron used was ferrous sulfate heptahydrate (FeSO4·7H2O) and vitamin A used was retinyl acetate. Results: Average hemoglobin level at baseline was 12.0±0.3 g dL–1. After a period of depletion, it decreased to 5.7±0.2 g dL–1. Average hemoglobin levels after treatment in the control rats (rats fed SF) was 11.6±0.2 g dL–1, rats that was given tempe fortified with iron had not reached the average level of 12.0 g dL–1 while rats that were given tempe fortified with iron+vitamin A SF+TFe271+VA15 and SF+TFe271+VA50 the average of hemoglobin levels were, respectively 12.2±0.1 and 12.4±0.2 g dL–1. ANCOVA test results showed that tempe fortified with iron and vitamin A significantly (p = 0.001) improved the level of hemoglobin (Hb). The highest average hemoglobin level was in the treatment group iron 271 ppm+vitamin A of 50 ppm. Conclusion: Iron and vitamin A fortification in tempe with ferrous sulfate heptahydrate (FeSO4·7H2O) 271 ppm and retinyl acetate 50 ppm may increase hemoglobin level in iron deficiency anemia rats.